HUBUNGAN SELF-CARE DENGAN KONTROL GLIKEMIK PADA PASIEN DIABETES MELITUS TIPE 2 DI KLINIK DOKTER KELUARGA - , ULFA NURUL FATIMAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Diabetes Mellitus (DM) is a group of symptoms that occurs to someone due to the increase of blood glucose level caused by absolute or relative lack of insulin. DM can increase risk of coronary heart disease, stroke, peripheral vascular disease, retinopathy, nephropathy, and neuropathy. Complications associated with diabetes can be prevented through good control of glycemic. Self-care is believed to be able to directly affect to glycemic control of DM type 2 patients. Objective: The study aimed to identify correlation between self-care and glycemic control of DM type 2 patients at the clinic of family physician. Method: The study was non experimental with cross sectional design. Subject of the study consisted of 30 DM type 2 patients registered as Prolanis participants at the clinic of family physician. Samples were taken through purposive sampling technique. Data were obtained through questionnaire of the Summary of Diabetes Self-Care Activities (SDSCA) and analyzed using chi square to identify strength of correlation between the two variables. Result: The result of the study showed that there was significant correlation between use of oral hypoglycemic drugs or insulin and fasting blood glucose level (p=0.020). There was significant correlation between physical activities and foot care and fasting blood glucose level (p > 0.05). Physical activities, use of oral hypoglycemic drugs or insulin and foot care had no significant correlation with blood glucose 2 hours post fasting (p > 0.05). Conclusion: There was significant correlation between use of oral hypoglycemic drugs or insulin and level of fasting blood glucose (p = 0.020).